Preparation and Utilization of Kapok Hull Carbon for the Removal of Rhodamine-B from Aqueous Solution - P. S. Syed Shabudeen; R. Venckatesh; S. Pattabhi (E-Journal of Chemistry)
A carbonaceous sorbent prepared from the indegeneous agricultural waste (which is facing solid waste disposal problem) Kapok Hull, by acid treatment was tested for its efficiency in removing basic dyes. Batch kinetic and isotherm experiments were conducted to determine the sorption and desorption of the Rhodamine-B from aqueous solution with activated carbon. The factors affecting the rate processes involved in the removal of dye for initial dye concentration, agitation time, and carbon dose and particle size have been studied at ambient temperature. The adsorption process followed first order rate kinetics. The first-order rate equation by Lagergren was tested on the kinetic data, and isotherm data was analyzed for possible agreement with the Langmuir and Freundlich adsorption isotherm equations. The intraparticle diffusion rate equation from which adsorption rate constants, diffusion rate constants and diffusion coefficients were determined. Intraparticle diffusion was found to be the rate-limiting step. The structural and morphological of activated carbon were characterized by XRD and SEM studies respectively.